Survival of Patin Fish (Pangasius sp.) Seeds with Palm Shell Activated Charcoal Treatment Transported in a Closed System: Sintasan Benih Ikan Patin (Pangasius sp.) dengan Perlakuan Arang Aktif Cangkang Sawit yang Ditransportasikan dengan Sistem Tertutup - Murtiadji, Wisnu; Gumiri, Sulmin; Jemi, Renhart (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, IPB University, 2020)
One of common problem in fishing industry is a high mortality rate of juvenile fish during transportation. The present research aimed to study the characteristics of palm oil activated carbon and its effect on the changes of water quality that can improve the survival rate of juvenile catfish (Pangasius sp.). During study, juvenile catfish was transported for 48 hours by a simulation in the room with two different treatments: water tanks supplied with granulated and powder activated carbon and one control. Results of FTIR analysis showed that the activated carbon contained several functional groups such as Alkanes, Carboxylic Acid and Amina. Activated carbon element content resulted from the SEM analysis consisted of C, O, Si, N, Zr, Cu, Al and K. After transformed as activated carbon, we found that water and organic C contents in oil palm shell decreased and, reversely, the ash content increased. The study revealed that the activated carbon powder was better to improve survival rate of juvenile catfish and maintain water quality compared to granule ones where the survival rates after 48 hour transportation were 47,5%, 11% and 0% with treatments of powdered activated carbon, granulated activated carbon and control, respectively.